Low-Voltage Mixed-Mode Analog Filter Using Multiple-Input Multiple-Output Operational Transconductance Amplifiers - Montree Kumngern; Fabian Khateb; Tomasz Kulej (My University, 2024)
This paper presents a novel mixed-mode, low-power, 1 V analog filter that uses multiple-input multiple-output operational transconductance amplifiers (MIMO-OTAs). This filter uses four OTAs, two grounded capacitors, and one grounded resistor and offers four modes, namely voltage, current, transconductance, and transimpedance modes. Each mode of operation provides non-inverting and inverting low-pass, high-pass, band-pass, band-stop, and all-pass filter transfer functions (10 transfer functions). Thus, in four operating modes, the designed filter offers 40 transfer functions, which is the full capability of a mixed universal filter. The natural frequency of all filter functions can be electronically controlled. To obtain the multi-input OTA, the multiple-input bulk-driven MOS transistor (MIBD-MOST) technique is used. This technique can reduce the number of MOS input differential pairs and the supply voltage. The active mixed-mode filter was simulated using a CMOS TSMC 0.18 μm process in the Cadence Virtuoso ADE Suite. The simulation results confirm the performance of the proposed filter.
Keywords: Transconductance; Operational transconductance amplifier; Mode (computer interface); Analog and Mixed-Signal Circuit Design